Status of nutrition labeling knowledge, attitude, and practice (KAP) of residents in the community and structural equation modeling analysis - Liao, Yinxia; Yang, Jianjun (Frontiers in Nutrition, 2023)
Objective: Unhealthy foods were a major contributor to the occurrence of chronic non-communicable diseases. The promotion of nutrition labeling in the community can effectively help residents to choose healthy foods, which plays an important role in the prevention of chronic diseases. However, the public awareness of this measure is not clear. Our study used a structural equation model based on KAP theory to analyze the interaction mechanisms among knowledge, attitude and practice, and aimed to evaluate the relationships among nutrition knowledge, attitude, and practice of residents, which can provide the basis of policy formulation for nutrition education and behavior intervention. Methods: We carried out a cross-sectional study from May to July, 2022 in “Community Health Service Center” and each “Community Service Station” in Yinchuan use a self-designed questionnaire and convenience sampling to evaluate resident nutrition labeling KAP status. This study adopted the structural equation modeling approach to analyze a survey of Chinese individuals through the cognitive processing model, interrelated nutrition knowledge, nutrition label knowledge, attitude and practice. Results: A total of 636 individuals were investigated. The score of nutrition knowledge of community residents was 7.48 ± 3.24, the passing rate was 19.4%. Most residents had a positive attitude towards nutrition labeling, but awareness rate was only 32.7% and utilization rate was 38.5%. Univariate analysis showed that women had higher knowledge scores than men (P<0.05), and young people had higher scores than the elderly (P<0.05), and the difference was significantly. Based on KAP structural equation model (SEM), residents’ nutrition knowledge will directly affect their attitudes towards nutrition labeling, and then affect their practice. Attitude plays an indirect effect in the process of cognition and practice of nutrition labeling. Conclusions: The nutrition knowledge and nutrition labeling knowledge of respondents hardly directly supports the practice of nutrition labeling, but it can influence the use behavior by forming positive attitudes; The KAP model is suitable for explaining residents’ use of nutrition labeling in the region. Future research should focus on better understanding the motivations of residents to use nutrition labeling and the opportunity to use nutrition labeling in real-world shopping settings.